Effect of a rising time of the lightning impulse on streamer discharge behavior - Ahmed, Noor A.; Khalaf, Thamir H. (Iraqi Journal of Science, 2025)
A numerical simulation of the streamer discharge was constructed to study the streamer origination (initiation) of the streamer discharge formation and development between two electrodes, one of which is a needle and the other a sphere electrode in transformer oil, with focusing on the effect of the rising time of lightning impulse voltage between the two electrodes. The model includes electron, positive, and negative ion continuity equations and Poisson's equation to simulate this streamer discharge behavior. The growth and development of the streamer discharge are examined by changing the rising time it takes for the voltage to increase using the applied impulse voltage parameters. Additionally, this model investigates different characteristics of the streamer discharge, such as the distribution of the electric field, time initiation of the streamer discharge at the electrode (needle), streamer discharge velocity, streamer diameter, and minimum breakdown voltage for each case of the rising time. The results showed that increasing the rising time (25-100ns), increasing the time initiation(6-19ns), and decreasing the streamer's electric field before it. (4.75 , decreases the streamer velocity (2.353-1.421km/s), the streamer diameter (0.175-0.167mm), and increases the voltage breakdown(79-100kv). The simulation was done in a virtual cell filled with transformer oil with a gap of 1mm between the two electrodes.